INTEGRATION OF BRANDI’S THEORY IN THE CONTEXT OF EASTERN RELIGIONS AND CULTURES - Capanna, Francesca (Protection of Cultural Heritage, 2019)
The Istituto Superiore per la Conservazione ed il Restauro (ISCR) has always been involved in the diffusion of Cesare Brandi’s restoration theory and practice in the international panorama. Since 1950 Brandi’s theory has spread through model interventions, scientific advice and the tutoring of international students. Those factors lead also to an increase of trust and esteem towards the ISCR. In the 21st century, the ISCR started to be involved in the establishment of new conservation schools by foreign countries. Moreover, it promoted translations of the “Teoria del Restauro” (theory of conservation) book in English, French, German, Spanish, Portuguese, Greek, Serbian, Russian, Chinese, Japanese and Polish. This permitted a deepened understanding and integration in the local culture of Brandi’s theory, rather than the direct execution of the fifties. For those reasons, today the Italian conservator-restorers face the new opportunity and growing perspective: looking at Brandi’s theory in direct contact with the cultural context in which is being applied, through the dialogue with local, highly trained professionals. The importance of this dialogue has become particularly evident during collaborations with eastern countries, with a particular interest in which part of the theory can merge and which will diverge with the religious and cultural principles. Especially, the experience of the ISCR in Ajanta in India (2004-2018) and Kathmandu in Nepal (after the 2013 earthquake) will be discussed.